Behavioural and psychological traits of 'Get-Rich-Quick Schemes' participants in Malaysia - Mazlan, Ahmad Rizal; Mohd. Othman, Fazilah; Mohtar, Shahimi; Zubir@Salim, Azlizaman (Hamdard Foundation Pakistan, 2020)
The purpose of this paper is to analyze the behavioural and psychological traits of getrich-quick schemes participants using Big Five Inventory (BFI) psychometric test. Design/Methodology/Approach – A sample of 400 respondents was randomly selected in various regions in Malaysia of which 200 of them have participated in GRQS and the other 200 have never participated. The Big Five Inventory (BFI) personality assessment instrument was used which consists of the five personality traits – openness, conscientiousness, extraversion, agreeableness and neuroticism. Findings – In general, men have a greater tendency to join GRQS than women; and the proportion of Malay respondents participated in GRQS is higher than other races. Those with lower academic qualification, above 30 years old and in the middle-income group also have relatively higher tendency to join GRQS compared to other comparable groups. For the BFI psychometric test, the t-test shows that the extroversion, conscientiousness and neuroticism levels of the participants are significantly different than the non-participants. Originality/Value – This is considered to be the first study to assess the personality traits of GRQS participants using BFI psychometric test, which enables the regulator such as the central bank to understand the behaviour and psychological traits of those who are prone to join a fraudulent investment scheme such as GRQS in Malaysia.